Design of a Linear Floating Active Resistor with Low Temperature Coefficient - Yu Liu; Pak Kwong Chan (Chips, 2025)
This paper presents the design and implementation of a linear, stable, low-power and PVT insensitive floating active resistor, which is realized using TSMC 40 nm CMOS process technology. By incorporating the automatic tuning circuit, this work has achieved improved performance metrics, which include low process sensitivity, reduced temperature coefficient, and good linearity. Monte Carlo (MC) simulations are conducted to evaluate the active resistor’s performance under variations in temperature, process, and supply voltage. The proposed design has demonstrated an average resistance process sensitivity of 0.64%, a temperature coefficient (T.C.) of 57 ppm/°C across −25 °C to 85 °C, and a linearity figure of merit (FOM) of 2.4 × 10−2 V−1 with a resistance close to MΩ level. It can achieve a linear resistance tuning range of 430.5 kΩ to 1.714 MΩ. The typical power consumption of a single active resistor is 0.25 µW at 2.1 V bootstrapped supply voltage through a Dickson charge pump (DCP) circuit using a DC input of 1 V. These results have confirmed that the proposed active resistor can function as a robust and efficient resistor for low-voltage integrated circuits and systems.